Fundamentalisme Islam, Krisis Modernitas dan Rekonstruksi Identitas - Chaider S. Bamualim (Refleksi: Jurnal Kajian Agama dan Filsafat, 2002)
Islamic fundamentalism, often associated with radical Islamism, has become a central issue in public discourse, particularly in post-reform Indonesia. The emergence of hardline Islamic groups, such as Laskar Jihad, Majelis Mujahidin Indonesia (MMI), and Front Pembela Islam (FPI), has raised concerns about the possible radicalization of Islam in a country known for its moderate traditions. This study provides a preliminary descriptive and analytical exploration of these movements within contemporary Indonesia. It begins with a general discussion of Islamic fundamentalism and then focuses on its specific manifestations in Indonesia’s current socio-political landscape. The paper aims to shed light on the dynamics of these groups, their ideological foundations, and their impact on Indonesia’s religious and political identity.